Peran Guru MDA Dan Orang Tua Dalam Mendisiplinkan Siswa Untuk Melaksanakan Didikan Subuh di MDTA Galuang - Faizah, Liz (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
The Role of MDA Teachers and Parents in Disciplining Students to Implement Dawn Education at MDTA Galuang. This research is based on the case of student discipline in attending dawn education including attendance. students come late even some students who have a turn to deliver. one of the lesson materials is absent, then discipline regarding concentration, there are students who do not listen, do not answer greetings, chat, play with friends beside them, there are even students who often take turns to go out while running with the excuse of going to the bathroom The attitude of fellow students, for example, likes to tease friends who sit beside him. took a friend's cap and beat his friend to change seats.This research uses qualitative descriptive research. This research is located in MDTA Galuang. In this study, the key informants are MDA teachers and. Parents of children who attend dawn education, data collection in this study through observation, interviews (Snow ball Sampling), and dolamentation. The data analysis technique that the author uses is data reduction. data presentation and data verification and to guarantee. the validity of this study the author triangulated the data. Based on the results of the research, it can be concluded as follows: first, the role of the MDA teacher in disciplining students to carry out the dawn education of some teachers is optimal, but there are teachers who do not carry out their role in disciplining children. Second, parents in disciplining their children have played a role, but there are parents who have not. perform its role well in training, guiding and motivating children at home. Third, the constraints faced by MDA teachers are difficulties in disciplining children: children's lack of parental cooperation at home, student delays. Obstacles faced by parents are difficulties in providing understanding, understanding of the importance of dawn education, in general difficulty in waking children up to attend dawn education